Nigella sativa and its derivative thymoquinone ameliorates the negative impact of cyclophosphamide on mouse male germ cells and embryo - Nadia Hanis Abdul Samat (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Chemotherapy drugs like cyclophosphamide (CPA) is an alkylating agent that can cause damage to the male germ cells and follicles of the gonads resulting in adverse reproductive problems and infertility. This study aims to investigate any potential to salvage the embryo from the toxic paternal exposure with the use of Nigella sativa extract (NSE) and thymoquinone (TQ). The survival and damage of embryos following fertilization from sperm exposed to CPA were studied in order to investigate the protective effects of NSE and TQ on male mice at 8 to 10 weeks of age according to the groupings as follows: i) control, ii) CPA only, iii) NSE only, iv) TQ only, v) CPA+NSE and vi) CPA+TQ, as well as supplementation of NSE (5mg/ml, 10mg/ml, and 15mg/ml) and TQ (1μM, 10μM and 100μM) in the culture media of developing embryo. Non-invasive embryo examination was based on simple methods of observation focused on morphology and dynamics of embryo development under the inverted microscope without fixation and staining. The level of embryo glucose uptake was then determined to evaluate the quality of the preimplantation embryos while quantitative polymerase chain reaction (Q-PCR) and immunofluorescence methods were employed to investigate the tendency of the embryos whether to survive or undergo apoptosis. In addition, the effects of NSE and TQ supplementation in the in vitro fertilization (IVF) culture media were also investigated. The results obtained from the preliminary study involving Balb/c has shown that the introduction to NSE and TQ have potential protective effects on the development of the embryo in vitro with a significant (p<0.05) in the percentage of motile sperm, number of fragmented DNA, sperm morphology, sperm head abnormalities and fertilization rate. NSE and TQ were also seen to improve the embryo quality in terms of embryo grading based on the fragmentation and structure of blastomere. The experiment using Swiss bred mice strain (ICR) has proved that treatment with NSE and TQ has a significant positive impact (p<0.05) on sperm motility, reduction in the number of abnormal sperm and percentage of sperm head abnormalities. Study on the embryo metabolites, indicates that there is no significant difference (p>0.05) in the level of glucose uptake in the culture media between the groups. In addition, molecular study which investigated the presence of five genes important in embryo development (Bcl-xL, BAX, SOX2, Oct4, and CD29), revealed that there are no significant differences (p>0.05) in the levels of gene expression. The molecular findings were confirmed with immunofluorescence staining of the embryo for the detection of Bcl-xL, BAX, and Oct4. NSE and TQ supplementation in the culture media showed no effect on the embryo quality. Results from the in vivo experiments demonstrated the potential of NSE and TQ in the paternal protection from the alkylating effects of CPA to allow for the normal development of the embryo.